Linearization of a Matrix Riccati Equation Associated to an Optimal Control Problem - Foued Zitouni; Mario Lefebvre (International Journal of Differential Equations)
The matrix Riccati equation that must be solved to obtain the solution to stochastic optimal control problems known as LQG homing is linearized for a class of processes. The results generalize a theorem proved by Whittle and the one-dimensional case already considered by the authors. A particular two-dimensional problem is solved explicitly.